The distributional impact of Covid-19: Geographic variation in mortality in England - Breen, R; Ermisch, J (Max Planck Institute for Demographic Research, 2021)
Background: By their nature, the impact of epidemics on mortality varies geographically, suggesting that the geographical impact of an epidemic implies a social impact. Objective: To examine the association between two measures of the social composition of a local area and age- and sex-standardised Covid-19 and other mortality in the period 1 March to 31 July 2020. The measures are how deprived an area is and what proportion of its population is non-white. Methods: Using spatial autoregressive regression we analyse geographical variation in age- and sex-standardised Covid-19 mortality among English local authorities between 1 March and 31 July 2020 in relation to measures of social composition, and we compare it with mortality from non-Covid sources in the same period, and with all-causes mortality in 2018. Results: Areas with higher social deprivation have a higher Covid-19 mortality rate, but the association is much weaker than between social deprivation and mortality rates more generally. An area’s proportion non-white has a strong positive association with Covid-19 mortality, in contrast to a negative association with 2020 non-Covid and with 2018 mortality. Conclusions: Covid-19 mortality is related to the social composition of areas in different ways than current non-Covid mortality or past mortality. Contribution: The paper provides the first demonstration of the distinct distributional impact of mortality in relation to the Covid-19 virus by the social composition of areas in England.